The long-term time course of septic arthritis - Rhys G. E. Clement; Seng J. Wong; Andrew Hall; Sarah E. M. Howie; A. H. R. W. Simpson (Bone & Joint Open, 2024)
Aims: The aims of this study were to: 1) report on a cohort of skeletally mature patients with native hip and knee septic arthritis over a 14-year period; 2) to determine the rate of joint failure in patients who had experienced an episode of hip or knee septic arthritis; and 3) to assess the outcome following septic arthritis relative to the infecting organism, whether those patients infected by Staphylococcus aureus would be more likely to have adverse outcomes than those infected by other organisms. Methods: All microbiological samples from joint aspirations between March 2000 and December 2014 at our institution were reviewed in order to identify cases of culture-proven septic arthritis. Cases in children (aged < 16 years) and prosthetic joints were excluded. Data were abstracted on age at diagnosis, sex, joint affected (hip or knee), type of organisms isolated, cause of septic arthritis, comorbidities within the Charlson Comorbidity Index (CCI), details of treatment, and outcome. Results: A total of 142 patients were confirmed to have had an episode of septic arthritis in a native hip (n = 17) or knee joint (n = 125). S. aureus accounted for 57.7% of all hip and knee joint infections. There were 13 inpatient deaths attributed to septic arthritis. The median age of the patients who died was 77.5 (46.9 to 92.2) and their median age-adjusted CCI was 8 (6 to 12). A failure of the joint occurred in 26 knees (21%) and nine hips (53%). Of the knee joints infected by S. aureus (n = 71), 23 knees (32%) went into failure of joint, whereas of those infected by other organisms (n = 54), only three knees (6%) failed. Conclusion: Based on our study findings, hip and knee septic arthritis long-term outcomes were substantially worse than their immediate outcome suggested. Failure of knee joint is 6.1 times more likely to occur in those infected with S. aureus. Cite this article: Bone Jt Open 2024;5(9):785–792.